Monitoring the Socio-Economic Conditions in Chile - Paula Giovagnoli; Georgina Pizzolitto; Julieta Trías (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This report describes the socio-economic situation in Chile based on a large set of distributional, labor and social statistics computed from microdata of the Encuesta de Caracterización Socioeconómica Nacional (CASEN) from 1990 to 2000. The report also draws from other data sources and the existing literature. Chile had an outstanding economic performance during the 1990s, in particular in the first half of the decade, achieving a remarkable reduction in poverty, which contrasts with the experience of its neighbors in the Southern Cone. Poverty reduction was mainly due to economic growth, since inequality has remained very high.
Keywords: D3; I32; O54; 330; income; poverty; inequality; education; labor; wage; employment; Chile